Analysis of Mobile Apps for Learning Grammar through Mobile Assisted Language Learning Approach - Ebrahim Panah; Muhammad Yasir Babar; Sedigheh Shakib; Anahita Ghanad (ALTSA Publisher, 2021)
The objective of the current study is to evaluate the recently developed mobile apps for learning and improving English grammar. This study selected 10 grammar apps ranked 3 and above by online users with a large number of installations. The study adapted a framework proposed by Supyan Hussin (2013) with four criteria: System, Program, Curriculum, and Language & Culture. Furthermore, information provided in Google Play Store App assessment in terms of App users’ Reviews, Ratings, and Downloads also was used to assess the selected grammar apps. First, the findings show that the grammar apps tend to teach grammar out of context, second, apps minimally adapt to the user’s skill sets. Third, the grammar apps rarely offer explanatory corrective feedback to the users. Fourth, some grammar apps have accuracy issue in terms content and typo. Despite pedagogical paradigm shift to communicative approaches to language learning, the assessed grammar apps are more behaviorists in nature where features of cognitivism and constructivism, and particularly connectivism approaches are rare. To better align with MALL, contextualized language, explanatory feedback, and adaptive technology need to be incorporated into these apps.